Dandelion-enriched diet of mothers alleviates lead-induced damages in liver of newborn rats - Gargouri, M.; Magné, C.; Ben Amara, I.; Ben Saad, H.; El Feki, A. (Cellular and Molecular Biology, 2017)
Lead (Pb) is a highly toxic metal present in the environment. It causes disturbances of several functions, including hematologic, renal, reproductive and nervous ones. Preventive or curative use of medicinal plants against these disorders may be a promising and safe therapeutic strategy. This study evaluated the hepatic toxic effects of prenatal exposure to lead in rats and the possible protective effect of dandelion (Taraxacum officinale) added to the diet. Female rats were given a normal diet (control) or a diet enriched with dandelion (treated). In addition, lead acetate was administered to half of the rats through drinking water from the 5th day of gestation until the 14th day postpartum. Lead toxicity was evaluated in their offspring by measuring body and liver weights, plasma biochemical parameters, liver damage, as well as protein content and activities of antioxidant enzymes in the liver tissues. Lead poisoning of mothers caused lead deposition in blood and stomach of their pups as well as hepatic tissue damages. Moreover, significant decreases in liver weight and protein content were found. Lead treatment caused oxidative stress and marked changes in the activity of antioxidant enzymes. However, no damages or biochemical changes were observed in puppies from the rats co-treated with lead and dandelion. These results indicate that supplementation of pregnant and lactating rats with dandelion protects their offspring against lead poisoning, likely through reduction of oxidative stress and liver damages.